A review on the potential impact of probiotics and prebiotics in enhancing health benefits - Nadeem, Rutaba; Imran, Ali; Wei, Calvin R.; Naz, Saima; Waheed, Wisha; Akram, Muhammad Arslan; Ahmed, Arisha; Tahir, Saleha; Islam, Fakhar; Befa Kinki, Abdela (Cogent food & agriculture, 2024)
Humans are exceptional reservoirs of species diversity to form complex microbiota that play a crucial role in human health by modulating metabolic processes and combating various diseases in the host. The microbiota is positively influenced by the consumption of probiotics and prebiotics, which are beneficial bacteria and indigestible foods, respectively, to promote their growth. Many fermented foods are sources of probiotic strains and plant-based oligosaccharides are well-known prebiotics. Probiotics and prebiotics are important for the treatment of immune system impairment, cancer, liver disorders, gastrointestinal disorders, type 2 diabetes, and obesity because of their immunomodulatory characteristics, supporting gut barrier function, promoting antimicrobial compounds, and modulating the immune response. The objective of this review is to highlight the potential impact of prebiotics and probiotics in modulating gut microbiota to enhance health benefits.